Strategi Komunikasi Pemasaran Digital Brand Kecantikan: Studi Kasus Brand Somethinc - Myori Syahputri Sinaga; Muhammad Husni Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid growth in the cosmetics and skin care industry is reflected in the increasing need and desire of people for beauty products. In intense competition, various local brand companies in Indonesia are trying to create inclusive skincare products, in line with the diverse skin nutritional needs of all levels of society. The aim of this research is to understand the forms and strategies of digital marketing communications, with a focus on Somehinc companies that emphasize consistency and positive relationships with customers. This research adopts a qualitative methodology with library research, which involves collecting information from various sources such as reference books, articles, notes and journals that are relevant to the problem being studied. The results of this research conclude that there are several main strategies carried out by somethinc, namely the use of advertising on somethinc's social media in the form of content. Furthermore, Somethinc also carried out an innovative strategy by holding a flash sale promo bundling package at a cheaper price than buying individual products. Not only that, somethinc also collaborates with influencers and makes local and foreign actors and actresses who have many fans as brand ambassadors. Finally, somethinc also provides platforms and marketing in various marketplaces such as Shoope, Tokopedia, Tiktok Shop, Zalora, Lazada, JD.ID, Blibli, and Bukalapak.